Odiseo y Bagdad: "Ulysse from Bagdad" de Eric‐Emmanuel Schmitt y "Les Sirènes de Bagdad" de Yasmina Khadra - Muñoz García de Iturrospe, María Teresa (2018)
This article examines the symbolic representation of the journey of the common hero and his relationship with Odysseus in "Les Sirènes de Bagdad" by Y. Khadra (2006) and "Ulysse from Bagdad" by É.‐E. Schmitt (2008) by analysing some common motifs: the title as allusion, the new setting and classical references mostly explicit and reiterated to inner exile, loss of identity the impossible return and hospitality
Keywords: Khadra, Yasmina -- 1955-; Homero; Ulises (Personaje mitológico)